INTERNALIZATION OF PUBLIC RELATION AND ISLAMIC EDUCATION VALUES IN THE SOCIAL RELIGIOUS TRADITION IN THE “TREUN U GAMPONG” PROGRAM FOR THE ACEH COMMUNITY - H Husaini; Wahyu Khafidah (Universitas Muhammadiyah Surakarta, 2022)
This Community Development title is consolidation of religious social programs in the people of gampong lamteh dayah kecamatan suka makmur aceh besar. The Religious Social Program has been running very well in Lamteh Dayah village. The Community Service Team only focuses on strengthening the programs so that they are sustainable in the Community. Some small obstacles were found in the realization of the program, especially regarding social psychology and political economy which were not yet well established. Regarding these problems, the Dedication team used the Participatory Action method to solve the problem. The team together with the community moves and plays a role to solve the problem. The result of this community service activity was the realization of a sustainable religious social program in Lamteh Dayah village.